EXPLORING EFL STUDENTS' VIEWS ON USING YOUTUBE VIDEOS FOR IMPROVING LISTENING SKILLS IN ENGLISH - Karim, Sayit Abdul; Ramli, Ramli; Rusmanto, Genta; Fadhila, Rendra Miftahul; Alamsyah, Danang Fauzi; Putra, Muhammad Ashari (English Review: Journal of English Education, 2023)
English videos on YouTube can be utilized as an alternative medium for learning listening subjects. This research attempts to explore EFL students’ perspectives on using English videos on YouTube as a learning medium to enhance students’ listening skills. A mix-method research design was used to explore students’ perceptions of using English video to enhance their listening skills. The data in this study were obtained from questionnaires and semi-structured interviews which were administered online to thirty-two students of the English Language Education Study Program (ELESP) at Universitas Teknologi Yogyakarta using a convenience sampling technique. The findings revealed that of 32 respondents, 31 of them viewed the English video platform on YouTube to help them a lot in learning listening subjects. Of 32 respondents, 30 of them utilized the platform for learning vocabulary. Of 32 respondents, 29 of them thought that their listening skills improved a lot after watching and listening to videos on YouTube.  It indicates that the majority of respondents have positive perceptions of the utilization of this platform because it helps them in facilitating their learning needs. However, 2 respondents disagree about the statements for some reasons.